Multimodaalne suhtlus keeleõppe ja -kasutuse teenistuses - Silvi Tenjes; Triin Lõbus; Leila Kubinyi; Ingrid Rummo; Dmitri Kulakov; Eva Ingerpuu-Rümmel (Eesti ja Soome-ugri Keeleteaduse Ajakiri, 2010)
In the present article an overview of the scientific study carried out by Tartu University’s Department of Estonian as a Foreign Language is given. We observe more closely the part of the department’s research which is performed in co-operation with MUSU group, including the collaboration with Institute of Germanic, Romance and Slavonic Languages and Literatures. These activities are supported by the Estonian Science Foundation (ETF) grant project. It is also important to mention the co-operation with the Nordic Universities in the framework of PlaceME project. The research topics of the doctoral students are implementing different methods of discourse studies for analysing the multimodal communication, communicative competences and communication strategies in the process of language learning and usage.